Fracture of a veneered-ZrO2 dental prosthesis from an inner thermal crack - Lohbauer, Ulrich; Belli, Renan; Arnetzl, Gerwin; Scherrer, Susanne S.; Quinn, George D. (Case Studies in Engineering Failure Analysis, 2014)
Here we describe the fractographic analysis of a veneer-ZrO2 single-unit dental prosthesis that fractured in a shell-like manner. Analysis of the retrieved fragment revealed that the crack originated in the bulk of the veneer from a thermal flaw located between two layers of the veneering material. Using the measured flaw plane we showed that the conditions of loading at fracture were complex and probably involved important tangential components.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Dental ceramics; Dental fractography; Dental prosthesis; Fracture; Thermal crack; Zirconia